Physicochemical and sensory characteristics of a caprine milk caramel with the inclusion of amaretto - Malavassi-Conejo, Pamela; Chacón-Villalobos, Alejandro; Víquez-Barrantes, Diana; Cordero-García, Marcia (Agronomía Mesoamericana, 2023)
Introduction. Worldwide, bovine dairy products are prevalent, so there is a need for studies focused on less traditional milk, such as goat milk. Objective. To evaluate the effect of two levels of inclusion of amaretto on the physicochemical and sensory characteristics of a goat milk caramel. Materials and methods. Between January and September 2017, at the Universidad de Costa Rica, milk caramels were made with two proportions (6 % and 9 %) of amaretto, which were selected using two focus groups, pH, Brix degrees, aw, texture, color, and sensory liking were evaluated. Results. The milk caramels with inclusion of 6 % and 9 % amaretto obtained the following characteristics respectively: 71.8 and 70.8 ºBrix, pH= 6.8 and 6.9, aw=0.8, hardness= 1.3 and 0.3, adhesiveness= 0.75 and 6.0, elasticity= 23.0 and 21.0, L*= 33.0 and 33.4, a*= 11.3 and 11.4, b*= 26.2, c*= 28.5 and 28.6, h*= 66.7 and 66.4, with an average liking of 7.3 and 7.7, and an average purchase intention of 6.9 and 7.2. The cluster analysis generated three groups of people: G1 = 25.5 % with a mean liking of 4.7 and 6.2 for the 6 % and 9 % formulations, respectively; G2 = 19.6 % with a mean liking of 8.5 and 5.5 for the 6 % and 9 % formulations, respectively; and G3 = 54.9 % with a mean liking of 8.2 and 9.1 for the 6 % and 9 % formulations, respectively. Conclusions. The inclusion of amaretto in the goat milk caramel turned out to be the product with the best profile. No significant differences were observed between the two liquor inclusion levels. The results suggest that both products had appropriate technical characteristics and taste.